Смислові інтенції сучасного спорту - Sheremet, Liubov (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2015)
The article is dedicated to the research into contemporary sport activity in the context of its semantic interpretations and its relation to the life-senses implied by society into sport, as well as its reflection in the value orientations being formed in human persons referred to this type of activity. In the course of the conducted analyses, the life-sense potential of sport is defined as a socially accepted and normative structure of values that finds its realization through human needs in the process of obtaining social acceptance by means of game activities that used to be traditionally considered as just an entertainment. Since the Modern Age sport games have been considered as adequate means for upbringing the youth and for fixing social norms and values in the human consciousness. The article argues that professional sport now is one of the most important ways of human socialization that also enables a human to achieve social mobility by mastering one’s social role and elevating one’s social status. Sport is shown to be the affirmation of normative masculinity on both athletes and spectators by attaching them, regardless of their gender identity, to a socially expected mode of behavior. It is proved that the most adequate definition of today’s sport would be considering it as a legitimate form of agonistics. Understanding the practice of sports as the ability to realize one of the most archaic human needs - the need for fight, active and direct competition in which the winner should always be detected is the basis of this definition. So sport realizes and sublimates human’s ancient urge for competition by replacing socially unaccepted forms of fight with civilized means for achieving and realizing one’s will to the victory.